2007
DOI: 10.1021/ja075261o
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Protein−Protein Interactions through Metal Coordination:  Assembly of a 16-Helix Bundle Protein

Abstract: Protein-protein interactions (PPI's) are central to nearly all processes within cells, whether they are formed transiently in dynamic networks or permanently in macromolecular assemblies. There has been considerable progress towards our understanding of how proteins recognize their partners and how the energetics of their interactions are tuned. 1 Nevertheless, the ability to predict or interfere with natural PPI's or engineer new ones remains a great challenge, owing to the fact that protein-protein docking p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
185
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(192 citation statements)
references
References 17 publications
1
185
0
3
Order By: Relevance
“…1B, Species 2 in Fig. 1A) (7,8). Such i, i þ 4 diHis motifs have been used for the assembly and stabilization of metalloproteins and peptides through coordination of divalent transition metal ions (9)(10)(11)(12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B, Species 2 in Fig. 1A) (7,8). Such i, i þ 4 diHis motifs have been used for the assembly and stabilization of metalloproteins and peptides through coordination of divalent transition metal ions (9)(10)(11)(12).…”
Section: Resultsmentioning
confidence: 99%
“…S3). Previous SV measurements on MBPC-1 indicated that the predominant species in solution at low protein and equimolar Zn concentrations was monomeric (7). Dimeric and tetrameric species become significantly populated only at MBPC-1 and Zn concentrations over 100 μM (1∶1 protein∶Zn) with increasing concentrations favoring the population of the tetrameric form.…”
Section: Redesign Of I2mentioning
confidence: 94%
“…Recently, the Tezcan (11) and Kuhlman (12) groups used rational and computational protein design methods, respectively, to engineer metal-dependent protein-protein interactions using conserved dihistidine metal-binding motifs from known metalloproteins. In each case, structural analysis of the engineered protein complexes suggested that, although metal-dependent assembly had been achieved, the metalbinding sites had not formed as desired (11,12). Although notable successes, these studies highlight the difficulty in precisely stabilizing the conformations of multiple amino acid side chains at once.…”
mentioning
confidence: 99%
“…[28,29] The resulting products favored dimers and tetramers often as mixtures, which could be tailored to favor a specific oligomer. Other groups have also employed various metal ion binding motifs to stabilize a designed protein motif; however, few are designed with the specific intent of controlling the oligomeric state.…”
mentioning
confidence: 99%